Lateral elbow instability - Harry Dominic Stracey Clitherow; Duncan Thomas McGuire; Gregory Ian Bain (Elsevier, 2014)
Lateral elbow stability utilises a combination of bony and soft tissue constraints. Lateral elbow instability is usually associated with an episode of elbow dislocation. Isolated lateral ligament complex insufficiency results in posterolateral rotatory instability (PLRI), The most common presentation is lateral elbow discomfort and a sensation of instability, without recurrent dislocation. The lateral pivot shift test is unreliable for diagnosing PLRI when the patient is awake due to significant apprehension. Stress radiographs, fluoroscopy, computed tomography and arthroscopy are all useful investigations to confirm the diagnosis of lateral instability. Surgical treatment is indicated for functional instability. All associated fractures need to be addressed. In severe cases, the medial structures and the posterolateral capsule may also require reconstruction.